Pengaruh Model Project based Learning dan Aktivitas Belajar terhadap Keterampilan Menulis Teks Negosiasi Siswa kelas X di SMAN 1 Pagai Utara Selatan Kabupaten Kepulauan Mentawai - Frida Nur Lestari; Yetty Morelent; Syofiani Syofiani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study examines the effect of Project Based Learning (PjBL) on students’ learning activities and negotiation text writing skills at the tenth-grade level of SMAN 1 Pagai Utara Selatan. The research employed a quantitative approach using a quasi-experimental method with a Solomon Four-Group Design. The sample consisted of 80 students divided into two experimental groups and two control groups. Data were collected through a learning activity questionnaire and a writing test, and analyzed using normality testing, homogeneity testing, paired sample t-test, and independent sample t-test at a 0.05 significance level. The results indicate that PjBL significantly improved students’ learning activities (p < 0.001). Within-group analysis showed a significant improvement in writing skills in the experimental group (p < 0.001). However, no statistically significant difference was found between the experimental and control groups in the posttest scores at the 5% level (p = 0.056), although the experimental group achieved a higher mean score. These findings suggest that PjBL effectively enhances learning engagement and contributes to improving negotiation text writing skills.